Everyday practice of science where intuition and passion meet objectivity and logic - Grinnell, Frederick (Oxford : Oxford University Press, 2009)
Frederick Grinnell presents an overview of the scientific process, or what he calls everyday practice of science. He provides students, young science professionals, and anyone interested in the science behind events in society with a feet-on-the-ground insider's view of how the practice of doing everyday science really works.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Science -- Methodology; Science -- Social aspects